Genotoxicity assessment of Garcinia achachairu Rusby (Clusiaceae) extract in mammalian cells in vivo - Marques, Eduardo de Souza [UNESP]; Silva, Suellen; Niero, Rivaldo; de Andrade, Sergio Faloni; Pires Rosa, Paulo Cesar; Perazzo, Fabio Ferreira; Maistro, Edson Luis [UNESP] (Elsevier B.V., 2012)
Ethnopharmacological relevance: Garcinia achachairu Rusby (Clusiaceae) is popularly known as "achachairu", and is used in Bolivian folk medicine for its healing, digestive, and laxative properties, and in the treatment of gastritis, rheumatism and inflammation. Despite its widespread therapeutic use, there is a lack of data regarding its in vivo genotoxic effects. Therefore, in this study, we used the comet assay and the micronucleus test, respectively, to evaluate the possible genotoxic and clastogenic effects of Garcinia achachairu seed extract (GAE) on different cells of mice.Material and methods: The GAE was administered by oral gavage at doses of 500, 1000 and 2000 mg/kg. For the analysis, the comet assay was performed on the leukocytes (collected 4 and 24 h after treatment), liver, bone marrow and testicular cells (collected 24 h after treatment), and the micronucleus test (MN) on bone marrow cells. Cytotoxicity was assessed by scoring 200 consecutive polychromatic (PCE) and normochromatic (NCE) erythrocytes (PCE/NCE ratio).Results and conclusion: The results showed that GAE did not induce significant DNA damage in leukocytes (4 h and 24 h samples), liver, bone marrow and testicular cells (24 h samples). GAE also did not show any significant increase in micronucleated polychromatic erythrocytes (MNPCEs) at the three tested doses. The PCE/NCE ratio indicated no cytotoxicity. Under our experimental conditions, the data obtained suggest that a single oral administration of G. achachairu extract does not cause genotoxicity and clastogenicity in different cells of mice. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Garcinia achachairu; Clusiaceae; Comet assay; Micronucleus test; Guttiferone A